Nilai Pendidikan dalam Novel Mahamimpi Anak Negeri Karya Suyatna Pamungkas: Tinjauan Sosiologi Sastra dan Relevansinya dalam Pembelajaran Sastra di SMA - Reshi, Ima Yustisia, Drs. Adyana Sunanda, M.Pd, Drs. Zainal Arifin, M.Hum (2017)
This study aims to: 1) describe the structure of the building works of the State Children's novel Mahamimpi Suyatna Pamungkas; 2) to reveal the value of education in the State Children's novel Mahamimpi Suyatna work Pamungkas approaches sociology of literature; and 3) revealed the relevance of these results to the study of literature in high school. This type of research is qualitative descriptive. The object of this study is the value of education in the State Children's novel works Suyatna Mahamimpi Pamungkas. Data of this study are words, phrases, clauses, sentences and paragraphs that reflect the structure and value of education in the novel. Data were analyzed using heuristic methods and hermeneutics. Based on the survey results revealed that the structure of the building Mahamimpi State Children's novel works Suyatna Pamungkas is the theme, plot, setting and characterization. Educational values contained in the work of the State Children's novel Mahamimpi Suyatna Pamungkas is the value of religious education, moral, social, nationalism. Relevance novel Mahamimpi State Children as teaching materials Indonesian learning in high school based on the educational values embodied in the novel (the angle of language, psychological, cultural background and educational value). Furthermore, there is a lack of compatibility between the novel as teaching materials with berthing competence and basic competences in Indonesian language teaching to high school. Keywords: the value of education, sociology of literature, learning Indonesian.